2018
DOI: 10.17576/jsm-2018-4708-14
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Carbazole Alkaloids and Coumarins from Aegle marmelos and Murraya koenigii and Their Antioxidant Properties

Abstract: In this paper, antioxidant properties of Aegle marmelos (stem bark, leaves) and Murraya koenigii (stem bark, root) were evaluated by 2,2-diphenyl-1-picrylhydrazy (DPPH) free radical scavenging, 2,2'-Azino-bis(3-ethylbenzthiozoline-6-sulfonic acid) (ABTS) decolourisation, cupric reducing antioxidant capacity (CUPRAC), ferric reducing antioxidant power (FRAP) and linoleic acid/β-carotene assays. The chloroform extract of Murraya koenigii stem bark was found to possess the highest antioxidant activity in CUPRAC (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 15 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…Thus, spectrophotometric variation of the solution's color (a decrease in absorbance at approximately 470 nm) is representative of the generation of lipid peroxides. The procedure, advantages, and disadvantages of this system have been extensively discussed in the literature [130][131][132][133][134][135][136][137][138], and some examples of the latest LPIP research employing this method are suggested [139][140][141][142][143][144][145][146][147][148][149].…”
Section: Watermentioning
confidence: 99%
“…Thus, spectrophotometric variation of the solution's color (a decrease in absorbance at approximately 470 nm) is representative of the generation of lipid peroxides. The procedure, advantages, and disadvantages of this system have been extensively discussed in the literature [130][131][132][133][134][135][136][137][138], and some examples of the latest LPIP research employing this method are suggested [139][140][141][142][143][144][145][146][147][148][149].…”
Section: Watermentioning
confidence: 99%
“…Naturally occurring compounds with anticancer effects have gained attention due to their low toxicity [ 3 ]. Murrayanine is a carbazole alkaloid derived from Murraya koenigii, which has been used in traditional Chinese medicine in the treatment of cancer [ 4 ] . Carbazole alkaloids have been shown to exhibit anticancer effects against a range of cancers [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…2,2‐diphenyl‐1‐picrylhydrazyl (DPPH) free radical‐scavenging activity was measured by adding samples (1 ml) with 2.9 ml of 0.15 mM methanolic DPPH solution, vortexed, and incubated in the dark for 2 hr at room temperature (Ng et al., 2018). Absorbance measurements were recorded at 517 nm in a 96 well microplate using a microplate spectrophotometer.…”
Section: Methodsmentioning
confidence: 99%
“…methanolic DPPH solution, vortexed, and incubated in the dark for 2 hr at room temperature (Ng et al, 2018). Absorbance measurements were recorded at 517 nm in a 96 well microplate using a microplate spectrophotometer.…”
Section: Dpph Free Radical Scavenging Activitymentioning
confidence: 99%